1993
DOI: 10.3109/02713689309020399
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecule expression in acute and fibrotic sympathetic ophthalmia

Abstract: Samples of iris ciliary body, choroid and retina from normal eyes and from 2 cases of sympathetic ophthalmitis (one acute and one late stage fibrosis) were examined for the expression of the VLA integrins beta 1 and alpha 1-6, and the integrin beta 3, in addition to ICAM-1, VCAM-1, ELAM-1 and CD44 using an APAAP staining technique. The expression of VLA-4, VLA-5, VCAM-1, ICAM-1, and CD44 was significantly increased and ELAM-1 was slightly increased in acute sympathetic ophthalmitis in comparison to fibrotic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The findings of this study may shed light onto the mechanisms of development of sympathetic ophthalmia, a very rare but one of the most intractable human eye diseases (Kuppner et al, 1993). The clinical manifestation of this disease may be acute or chronic, and involves infiltration of lymphocytes, plasma cells, and epithelioid cells in the choroid, thus resulting in uveitis, particularly in the choroid.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The findings of this study may shed light onto the mechanisms of development of sympathetic ophthalmia, a very rare but one of the most intractable human eye diseases (Kuppner et al, 1993). The clinical manifestation of this disease may be acute or chronic, and involves infiltration of lymphocytes, plasma cells, and epithelioid cells in the choroid, thus resulting in uveitis, particularly in the choroid.…”
Section: Discussionmentioning
confidence: 80%
“…The clinical manifestation of this disease may be acute or chronic, and involves infiltration of lymphocytes, plasma cells, and epithelioid cells in the choroid, thus resulting in uveitis, particularly in the choroid. In addition, a number of cell-adhesion molecules are expressed indicating lymphocyte activation and immigration (Kuppner et al, 1993). A model of traumatically induced sympathetic ophthalmia has been developed in mice.…”
Section: Discussionmentioning
confidence: 99%
“…MHC-II up-regulation in the contralateral retinal glial cells suggests that immunologically-mediated processes take place in the contralateral retinas (Gallego et al, 2012). Thirdly, in humans, sympathetic ophthalmia (Kuppner et al, 1993) develops in the contralateral eye after severe infection and massive trauma to one eye, and is due to inflammation activated by exposure to autoantigens. In addition, mechanism underlying the eccentric disparity in contralateral retina remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion molecules displayed on the macrophages and vascular endothe lium may also contribute to the development of granulomatous inflammation. 6 The metabolic products released at the site of inflammation are found either to accentuate granu loma development or to suppress formation of epithelioid cell granulomas and the associated chronic inflammatory process.12 Studies on experi mental granulomatous uveitis have revealed enhancement of the granulomatous process in the presence of lip oxygenase metabolic products of AA. In contrast cyclo-oxygenase products are noted to suppress granuloma formation.lO Such modulation of granulomatous inflammation in the presence of AA metabolites could be the result of altered macro phage expression of MHC class II molecules.…”
Section: Granulomatous Inflammations Of the Uveamentioning
confidence: 99%